CAPABILITY OF WATER AND ETHYL ACETATE EXTRACT FRACTIONS OF BENALU (Dendrophthoe pentandra L. Miq) LEAVES TO DISSOLVE CALCIUM KIDNEY STONE IN VITRO, DETERMINED USING FAST NEUTRON ACTIVATION METHOD - Sasmito .; Darsono . (Indonesian Journal of Pharmacy, 2001)
Kidney stone disease is common among Indonesian. Dendrophthoe pentandra L. Miq grow on petai (Lauchaena glauca L.), a plant parasite has yet been used as traditional medicine to treat, especially, kidney stone disiase. Fat free Dendrophthoe pentandra L. Miq leaves powder was macerated using ethanol (70%) followed by ethyl acetate. The compound content in water and ethyl acetate fractions were analyzed by thin layer chromatography (TLC) using cellulose as the stationary phase and a mixture of butanol: acetic acid: water (4:1:5) as mobile phase. The TLC data showed that water and ethyl acetate fractions contained flavonoid compounds. Kidney stone was analyzed using Infra Red Spectrophotometer to identify its chemical contents. The result showed that the kidney stone consisted of calcium and magnesium carbonate/phosphate. The Fast Neutron Activation analysis was utilised to determine the solubility of kidney stone. The result demonstrated that the maximum solubility of kidney stone was achieved in water fraction with the concentration of 90 % or in ethyl acetate fraction with the concentration of 70 %. The solubility of kidney stone in water fraction was higher than that in ethyl acetate fraction. Key word : Kidney stone, Dendrophthoe pentandra, Water fraction, Ethyl acetat fraction.